ANALYSIS OF FACTORS AFFECTING THE DURATION OF AUDIT COMPLETION AT PT GARUDA INDONESIA TBK - Windy Indriyani; Nurul Shofiyah; Diana Dewi; Nurul Adhani Ilham; Sri Nurdewi Sartika Astuti (RADJA PUBLIKA, 2025)
This study investigates the elements that influence the audit completion time (Audit Report Lag/ARL) at PT Garuda Indonesia Tbk during the 2020–2024 period by applying a descriptive qualitative approach through case analysis. The study shows that ARL has three key elements, namely financial statement complexity, the company's financial condition (financial distress), and regulatory influence. The high complexity of financial statements and financial pressure due to the pandemic lengthen audit time, while strict supervision from the Financial Services Authority (OJK) and the Ministry of State-Owned Enterprises (SOEs) encourages compliance in reporting. ARL at Garuda has decreased drastically from 196 days in 2020 to 84 days in 2024, indicating progress in governance and efficiency of the audit process. The results of this study confirm that ARL reflects the interaction between internal and external factors in the preparation of financial statements. Keywords: Audit Report Lag, financial statement complexity, financial distress, regulatory pressure, PT Garuda Indonesia Tbk.